Knowledge and Attitudes of Young People toward Mental Illness: A Cross Sectional Study. Issue 4 (1st October 2020) - Al Omari, Omar; Wynaden, Dianne; Alkhawaldeh, Abdullah; Al-Delaimy, Wael; Heslop, Karen; Al Dameery, Khloud; Bani Salameh, Ayman
ABSTRACT: The aim of the study was to investigate young Jordanians' knowledge and attitudes toward people who have a mental illness. A cross sectional design was utilized. A convenient sample of 858 participants aged between 15–24 years old completed a survey. Participants under 19 years were accessed through their schools and those 19 years and above were accessed through universities. Results showed that although the majority of university and school students' responses were generally consistent, they disagreed on 11 items on the survey; for example, 186 (39.3%) of university students agreed that mental illness has a biological origin compared with only 119 (30%) of school students. The majority of young people 737 (85.9%) were willing to learn and 792 (92.3%) felt that they have to help people with mental illness, which make them willing to learn. In conclusion, the findings provide insights for decision makers and researchers in Jordan about young peoples' knowledge and attitudes toward mental illness. Increasing young adults' literacy through introducing educational programs such as mental health first aid courses will enrich their knowledge; help change attitudes and reduce stigma toward people living with mental illness.